ANALISIS PENGARUH JUDI ONLINE TERHADAP PEREKONOMIAN MASYARAKAT DI KOTA PAREPARE - ACHMAD RAMADHAN (IAIN Parepare, 2024)
This research aims to provide an explanation of the impact of online gambling on the community's economy which can be disrupted and damaged when online gambling has taken over society, especially middle and lower class society subdistrict, Ujung. The research method used by researchers is the qualitative method. The research results show that there are 4 effects of online gambling on the community's economy, namely the impact on wealth, excessive addiction, feelings of laziness that arise due to online gambling, decreased purchasing power. The conclusion resulting from this research is that people are expected to be able to control themselves against the temptation of online gambling and the government and police are expected to be able to overcome the rise of dangerous online gambling while also having a direct impact on the community's economy.